Role Ambiguity and Work Family Conflict on Job Stress of Banking Employees in Bengkulu City - Sri Ekowati; Tezar Arianto; Ririn Harini (Universitas Mercu Buana, 2025)
Objectives: The objective of this study is to analyze the effect of role ambiguity and work-family conflict on job stress among banking employees in Bengkulu City.Methodology: The study used a quantitative approach with data collected from 180 respondents through purposive sampling. The participants were permanent or contract banking employees with a minimum of one year of work experience. Data analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS). Validity and reliability tests were performed, including AVE (>0.50), Composite Reliability (CR), and Cronbach’s Alpha (>0.70).Finding: All indicators met the validity and reliability criteria: The AVE values were: Role Ambiguity (0.76), Work-Family Conflict (0.74), and Job Stress (0.77). The R-Square (R²) value for Job Stress was 0.578, indicating that 57.8% of job stress variability can be explained by role ambiguity and work-family conflict. Hypothesis testing showed: Role Ambiguity had a positive and significant effect on Job Stress (β = 0.429, t = 6.215, p = 0.000), Work-Family Conflict had a positive and significant effect on Job Stress (β = 0.378, t = 5.801, p = 0.000).Conclusion: The study concludes that both role ambiguity and work-family conflict significantly increase job stress among banking employees. To mitigate this, bank management should focus on clarifying employee roles and providing programs that support work-life balance.